A new procedure for preparation of Sulfon-Z compounds. - H. K. Al- Daraji , Alaa (University of Thi-Qar Journal of Science, 2019)
Four compounds (Sulfon – Z) were prepared by a new procedure where Z is; N, S, O, and relating moieties. This procedure have many advantages comparing with other methods, its simple and easy, short time for preparation process (45 minutes in maximum), available starting materials (such as compounds; A, B, C, and others), cheap, relativily high percentage yield ( 60 – 96 %). However, above points are depending on the nature of starting materials. The products were identified by; melting point, thin- layer chromatography technique and Infra-red spectra. In addition, biological activity of these compounds have been studied against three different species (St.aureus, E . coli and Candida albicans